Lessons learned through the implementation of a rural longitudinal integrated clerkship at the University of Missouri-Columbia - Meghan Meyers; Jana Porter; Laura Morris; Whitney Lefevre (James Cook University, 2023)
Introduction: Created in 1995, The University of Missouri School of Medicine’s Rural Track Pipeline Program was designed to address physician shortages in rural Missouri through medical student participation in a series of clinical and non-clinical programs over the course of their medical training to influence graduates to choose rural practice.Methods: To increase the likelihood of students choosing rural practice, a 46-week longitudinal integrated clerkship (LIC) was implemented at one of nine existing rural training sites. Over the course of the academic year, quantitative and qualitative data was collected to evaluate effectiveness of the curriculum and for quality improvement purposes.Results: Data collection is in progress and includes student evaluation of the clerkship, faculty evaluations of students, student evaluations of faculty, student aggregate clerkship performance, and qualitative data from student and faculty debrief sessions.Discussion: Based on data collected, changes are being made to the curriculum for the following academic year to enhance the student experience. The LIC will also be offered at an additional rural training site beginning in June of 2022, and then expanded to a third site in June of 2023. As each LIC is unique, our hope is our experience and lessons learned will help others in developing a LIC or improving an existing LIC.